1995
DOI: 10.1016/0008-6363(95)00076-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased resistance to ischaemic injury in the isolated perfused atherosclerotic heart of the cholesterol-fed rabbit

Abstract: Hearts from CFR exhibited markedly improved recovery upon reperfusion compared to age-matched controls, strongly suggesting increased myocardial resistance to ischaemic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 0 publications
3
15
1
1
Order By: Relevance
“…The maximal contractility which could be reached at the higher pacing rate and higher [Ca 2+ ] o was lower in papillary muscle from HC rabbits. This result is consistent with the finding of Le Grand et al [17] that the isovolumetric left ventricular pressure that developed was significantly lower in hearts from cholesterol-fed rabbits than that in agematched controls. Peterson et al [24] also demonstrated that the rate of tension development is lower and the force-velocity relationship is suppressed in papillary muscle isolated from hypercholesterolemic rabbits.…”
Section: Hypercholesterolemic Effect On Myocardial Contractilitysupporting
confidence: 83%
“…The maximal contractility which could be reached at the higher pacing rate and higher [Ca 2+ ] o was lower in papillary muscle from HC rabbits. This result is consistent with the finding of Le Grand et al [17] that the isovolumetric left ventricular pressure that developed was significantly lower in hearts from cholesterol-fed rabbits than that in agematched controls. Peterson et al [24] also demonstrated that the rate of tension development is lower and the force-velocity relationship is suppressed in papillary muscle isolated from hypercholesterolemic rabbits.…”
Section: Hypercholesterolemic Effect On Myocardial Contractilitysupporting
confidence: 83%
“…It has been shown that atherosclerosis is associated with functional abnormalities in the vascular contractile response in animal models [4,8,10,19], and that in rabbits fed high-cholesterol diets, the baseline spontaneous heart rate, left ventricular developed pressure and coronary flow were lower than those of age-matched controls [7]. We also found that the positive inotropic response to ISO was reduced in papillary muscle from HC rabbits in this study.…”
Section: Cholesterol and Myocardial Contractilitysupporting
confidence: 70%
“…In hearts isolated from rats fed 2% cholesterol-enriched diet for 24 weeks, baseline left ventricular end-diastolic pressure was elevated; however, ischemic and postischemic cardiac functional parameters were not significantly impaired . In hearts isolated from rabbits after a 6-week feeding with 2% cholesterol, although preischemic cardiac contractile function was significantly lower, no significant differences were observed upon reperfusion compared with controls (Le Grand et al, 1995). The reason that hyperlipidemia in some ex vivo rat and rabbit heart models and in LDLr Ϫ/Ϫ mice may not significantly impair or may even improve recovery of postischemic contractile function, especially after a long-term high-cholesterol diet, is not known.…”
Section: Hyperlipidemia and Atherosclerosismentioning
confidence: 99%